Inter-organisational costing approaches: the inhibiting factors - Bastl, Marko; Grubic, Tonci; Templar, Simon; Harrison, Alan; Fan, Ip-Shing (Mcb, 2010)
Purpose - The purpose of this paper is to highlight the limitations of current accounting practices in an inter-organisational context; introduce contemporary costing approaches used in inter-organisational costing (IOC) programmes; and identify the inhibitors of successful implementation of IOC programmes. Design/ methodology/approach - The paper uses a structured review of empirical and theoretical literature. Findings - Traditional accounting practices do not adequately fulfil their role in the inter-organisational context. Contemporary accounting practices overcome only some limitations of traditional accounting practices. The paper uncovers part of the complexity surrounding the implementation of IOC programmes and suggests that we are dealing with a broad inter-disciplinary phenomenon. Research limitations/implications - Conclusions are drawn on a conceptual level and further empirical investigation is encouraged. Practical implications - The paper raises the awareness of the complexity surrounding the implementation of IOC programmes. The broad set of inhibiting factors could be effectively used by managers to assess the readiness of organisations involved in implementation of IOC programmes. Originality/value - This research is the first that systematically addresses the problem of inhibitors in the implementation of IOC programmes. The broad scope of the paper sets the foundations for more focused research into specific inhibiting factors.
Keywords: Operating costs Organizational economics Supply chain management supply chain management integration information networks adoption systems trust